Effectiveness of nurse‐delivered screening and brief alcohol intervention in the workplace: A randomized controlled trial at five Japan‐based companies. (2nd August 2022) - Kuwabara, Yuki; Kinjo, Aya; Fujii, Maya; Minobe, Ruriko; Maesato, Hitoshi; Higuchi, Susumu; Yoshimoto, Hisashi; Jike, Maki; Otsuka, Yuichiro; Itani, Osamu; Kaneita, Yoshitaka; Kanda, Hideyuki; et al.
Abstract: Background: Excessive alcohol use is a leading cause of global morbidity and premature mortality. This study evaluated the effectiveness of two types of nurse‐delivered interventions to reduce excessive alcohol consumption among screened participants using the alcohol use disorders identification test (AUDIT) in the workplace. Methods: A randomized controlled trial involving AUDIT‐positive employees of five Japan‐based companies was conducted. A total of 351 participants were randomized into groups that received a patient information leaflet (PIL), 5 min of brief advice, or 15 min of brief advice and counseling. Outcomes (weekly alcohol consumption and drinking and binge drinking frequency in the previous 30 days) were evaluated at 6 and 12‐month follow‐up. Results: The follow‐up rates were 96.3% ( n  = 338) and 94.9% ( n  = 333) at 6 and 12 months, respectively. At 6 months, the mean change in weekly alcohol consumption was −38.1 g (−1.64 US fluid oz/week) in the 15‐min brief advice and counseling group, which differed significantly from the PIL group. The reduction in the advice and counseling group persisted at 12‐month follow‐up but was no longer significantly different from the PIL group. There was no significant change in alcohol consumption observed in the 5‐min brief advice group. Improvement in drinking and binge drinking frequency was observed in all three groups. Conclusions: Nurse‐delivered 15‐min brief advice and counseling was effective over a 6‐month period in reducing alcohol consumption in a workplace setting. This finding suggests that the implementation of workplace screening and brief intervention could play a useful role in preventing the burden of harmful alcohol use. Abstract : This randomized controlled trial evaluated the effectiveness of two types of nurse‐delivered interventions in the workplace. At six months, the weekly alcohol consumption significantly decreased in the 15‐min brief advice and counseling group. The mean change in alcohol consumption (‐38.1 g/week (‐1.64 US fluid ounce/week)) in the 15‐min intervention group differed significantly relative to the control group. However, no significant change was observed in the 5‐min brief advice group. Improvement in drinking and binge drinking frequency was observed in all three groups.